Opening and closure forces of sliding mechanisms of different self-ligating brackets - Paola GANDINI; Linda ORSI; Maria Francesca SFONDRINI; Andrea SCRIBANTE (University of São Paulo, 2013)
Self-ligating brackets engage the wire by means of a slide mechanism. Forces that have to be applied to open and close the sliding mechanism of brackets are still unknown. Objective The aim of this study was to measure and compare the opening and closure forces of different self-ligating brackets. Material and Methods Three different stainless steel self-ligating brackets (Carriere LX, Ortho Organizers; F1000, Leone; Damon Q, Ormco) were tested. For each different bracket, 20 maxillary right central incisors and 20 mandibular right central incisors were used. Opening and closure forces were measured using an Instron Universal Testing Machine. Statistical analysis was performed and ANOVA and Tukey tests were carried out. Results Opening forces were registered between 1.1 N and 5.6 N, whereas closure forces were recorded between 1.57 N and 4.87 N. Significant differences were detected among the different brackets and between the two prescriptions tested. Conclusion The knowledge of different opening and closure forces of self-ligating brackets can help the orthodontist in the clinical management of these devices.